2019
DOI: 10.1002/jcla.23051
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress enhances the immune response to oxidatively modified catalase enzyme in patients with Graves’ disease

Abstract: Background Oxidative stress is associated with several autoimmune disorders and oxidative modification of proteins that may result in autoimmune response. This study aims to evaluate the catalase (CAT) activity and the autoimmune response against the native CAT and the oxidatively modified enzyme in patients with Graves' disease (GD) and healthy controls in a comparative way. Methods The CAT activity was evaluated via spectrophotometric method. Using enzyme‐linked immunosorbent assay, the reactivities of autoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
3
0
3
Order By: Relevance
“…in gd patients this phenomenon had a positive correlation with FT3 levels. 86 gargouri et al 87 also demonstrated a positive correlation between T3 levels and the immunoreactivity towards Mdamodified catalase in GD patients vs. controls. in a study by choi et al, 88 Mda and 8-hydroxy-2'deoxyquanosine (8-oHdg), H 2 o 2 and intracellular superoxide anion levels were measured in the tear fluid of GD patients.…”
Section: Autoimmunity Cancer and Oxidative Stressmentioning
confidence: 88%
“…in gd patients this phenomenon had a positive correlation with FT3 levels. 86 gargouri et al 87 also demonstrated a positive correlation between T3 levels and the immunoreactivity towards Mdamodified catalase in GD patients vs. controls. in a study by choi et al, 88 Mda and 8-hydroxy-2'deoxyquanosine (8-oHdg), H 2 o 2 and intracellular superoxide anion levels were measured in the tear fluid of GD patients.…”
Section: Autoimmunity Cancer and Oxidative Stressmentioning
confidence: 88%
“…Thus, altered molecules, with sufficient homology to the native protein antigens, can result in the production of specific autoantibodies and lead to the development of AD[41, 42,44,[54][55][56][57][58][59][60][61][62][63][64]. Systemic autoimmune rheumatic diseases (SARDs) are an important group of ADs.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen has a deleterious effect on biomolecules in the form of free radical and reactive oxygen species (ROS) [ 105 ], and many viruses have been demonstrated to cause cell damage by generating ROS and changing redox homeostasis [ 106 , 107 , 108 , 109 ]. The body can defend itself against ROS by using enzymes such as SOD, CAT, and GSH-Px [ 110 , 111 , 112 ]. MDA is the principal product of polyunsaturated fatty acid peroxidation, which is considered a highly toxic molecule and a marker of lipid peroxidation [ 113 ].…”
Section: Discussionmentioning
confidence: 99%